Effects of early postnatal gastric and colonic microbiota transplantation on piglet gut health - Christina Larsen; Simone Margaard Offersen; Anders Brunse; Mattia Pirolo; Soumya Kanti Kar; Luca Guadabassi; Thomas Thymann (Journal of Animal Science and Biotechnology, 2023)
Abstract Background Diarrhea is a major cause of reduced growth and mortality in piglets during the suckling and weaning periods and poses a major threat to the global pig industry. Diarrhea and gut dysbiosis may in part be prevented via improved early postnatal microbial colonization of the gut. To secure better postnatal gut colonization, we hypothesized that transplantation of colonic or gastric content from healthy donors to newborn recipients would prevent diarrhea in the recipients in the post-weaning period. Our objective was to examine the impact of transplanting colonic or gastric content on health and growth parameters and paraclinical parameters in recipient single-housed piglets exposed to a weaning transition and challenged with enterotoxigenic Escherichia coli (ETEC). Methods Seventy-two 1-day-old piglets were randomized to four groups: colonic microbiota transplantation (CMT, n = 18), colonic content filtrate transplantation (CcFT, n = 18), gastric microbiota transplantation (GMT, n = 18), or saline (CON, n = 18). Inoculations were given on d 2 and 3 of life, and all piglets were milk-fed until weaning (d 20) and shortly after challenged with ETEC (d 24). We assessed growth, diarrhea prevalence, ETEC concentration, organ weight, blood parameters, small intestinal morphology and histology, gut mucosal function, and microbiota composition and diversity. Results Episodes of diarrhea were seen in all groups during both the milk- and the solid-feeding phase, possibly due to stress associated with single housing. However, CcFT showed lower diarrhea prevalence on d 27, 28, and 29 compared to CON (all P < 0.05). CcFT also showed a lower ETEC prevalence on d 27 (P < 0.05). CMT showed a higher alpha diversity and a difference in beta diversity compared to CON (P < 0.05). Growth and other paraclinical endpoints were similar across groups. Conclusion In conclusion, only CcFT reduced ETEC-related post-weaning diarrhea. However, the protective effect was marginal, suggesting that higher doses, more effective modalities of administration, longer treatment periods, and better donor quality should be explored by future research to optimize the protective effects of transplantation.